Triangular cord sign and ultrasound features of the gall bladder in infants with biliary atresia - Visrutaratna P. (2014)
The aim of this study was to reassess the accuracy of the triangular cord sign, the triangular cord sign coupled with abnormal gall-bladder length, and an irregular gall-bladder wall in the diagnosis of biliary atresia. The ultrasonograms of 46 infants with cholestatic jaundice were reviewed for the triangular cord sign, gall-bladder length and gall-bladder wall without knowledge of the clinical data. Of the 23 infants with biliary atresia, 22 had the triangular cord sign whereas 17 infants with other causes of cholestatic jaundice did not have the triangular cord sign. The sensitivity, specificity, accuracy and positive predictive value of the triangular cord sign in the diagnosis of biliary atresia were 95.7, 73.9, 84.8 and 78.6%, respectively. The sensitivity, specificity, accuracy and positive predictive value of the triangular cord sign coupled with abnormal gall-bladder length in the diagnosis of biliary atresia were all 95.7%. Gall-bladder wall irregularity was seen in seven of 14 infants (50%) with biliary atresia whose gall bladders contained bile on ultrasound and in two of 22 infants (9.1%) without biliary atresia whose gall bladders contained bile on ultrasound. At the medical centre where this study was performed and where infants present with cholestatic jaundice at an advanced stage, the ultrasonographic triangular cord sign coupled with abnormal gall-bladder length is more reliable than the ultrasonographic triangular cord sign a lone or gall-bladder wall irregularity in the diagnosis of biliary atresia.